Psychotic disorders of space and time – A contribution of Erwin W. Straus - Moskalewicz, Marcin; Fuchs, Thomas (Frontiers in Psychiatry, 2023)
This paper presents and discusses a manuscript by one of the core founders of phenomenological psychopathology, Erwin W. Straus, concerning psychotic disorders of space and time (see attached Supplementary material). Written in June 1946, the manuscript is published for the first time as supplementary material to this paper. It is a clinical case-study of a patient with psychotic depression from Henry Phipps Clinic. It contains themes known from both Straus’ earlier and later work on lived time and mental illness, in particular a critique of physicalism in psychology, a vindication of primary sensing, a description of the spatiotemporal unity of lived experience, and the notion of temporal becoming. However, it is the only work by Straus that explores in such detail a patient’s case and shows how the lived experience is spatiotemporally structured and intrinsically related to affectivity, embodiment, and action. The manuscript is yet another piece of evidence of Straus’ significance in developing the field of phenomenological psychiatry in both Germany and the United States.